Staff Profile: Mr. Pius Gitonga Gervasioh - Gitonga, Pius (My University, 2016)
Pius Gitonga is a tutorial fellow in the school of nursing, University of Embu where he is currently teaching various undergraduate courses. He holds a Master’s Degree in Nursing Education; acquired from Kenya Methodist University. He is a PhD (Nursing Education and Administration) candidate in the University of Nairobi. His research interests are in the area of nursing education, empathy, adaptation and self-sufficiency